The improved oval forceps suture-guiding method for minimally invasive Achilles tendon repair. Issue 6 (June 2018) - Liu, Yang; Lin, Lixiang; Lin, Chuanlu; Weng, Qihao; Hong, Jianjun
Abstract: Objective: To discuss the effect and advantage of the improved oval forceps suture-guiding method combined with anchor nail in the treatment of acute Achilles tendon rupture. Methods: A retrospective research was performed on 35 cases of acute Achilles tendon rupture treated with the improved oval forceps suture-guiding method from January 2013 to October 2016. Instead of the Achillon device, we perform the Achillon technique with the use of simple oval forceps, combined with absorbable anchor nail, percutaneously to repair the acute Achilles tendon rupture. Results: All patients were followed up for at least 12 months (range, 12–19 months), and all the patients underwent successful repair of their acute Achilles tendon rupture using the improved oval forceps suture-guiding method without any major intra- or postoperative complications. All the patients returned to work with pre-injury levels of activity at a mean of 12.51 ± 0.76 weeks. Mean AOFAS ankle-hindfoot scores improved from 63.95 (range, 51–78) preoperatively to 98.59 (range, 91–100) at last follow-up. This was statistically significant difference ( P < 0.001 ). Mean Achilles Tendon Total Rupture Score (ATRS) at final follow-up was 94.87 (range, 90–100). Conclusion: The improved oval forceps suture-guiding method could make the advantage of minimally invasive repair with less complications, reduced surgical time and similar functional outcomes compared with the traditional open surgery. In addition, our new technique could save the cost of surgery with the compare of the Achillon device. At the same time for the cases which the remote broken tendon ends were within 2 cm from the calcaneal nodules, because of the less tendon tissue was left in the remote side, traditional percutaneous methods are incapable to ensure the reconstruction strength. By using the anchor nail, the improved technique has better repair capacity and expands the operation indication of oval forceps method.